Does it matter where I work? Examining the effect of Remote Work on employees’ Work Engagement and Burnout - Tau, Lebogang Tlotlo (University of the Witwatersrand, Johannesburg, 2023)
The global COVID-19 pandemic caused a significant shift in how and where work is conducted. Governments around the world initiated national lockdowns to enforce certain restrictions to curb the spread of infection and keep society functioning as normal. Businesses and institutions had to adopt flexible, remote working arrangements to achieve their ends during the pandemic. This study examined if remote work had any effect on employees’ work engagement and burnout, and if this relationship would be moderated or mediated by work overload and organisational support in South African organisations. A cross-sectional questionnaire design was utilized to obtain data from the sample. A sample of 103 employees from different organisations in South Africa participated in the study. Work overload and organisational support was measured using their respect subscales on the Job Demands-Resource scale. The Utrecht Work Engagement Scale, Oldenburg Burnout Inventory were used to measure the work engagement and burnout respectively. The results indicate that remote work does not predict both work engagement and burnout, nor was this relationship moderated by work overload and organisational support.
A research report submitted to the Faculty of Humanities, in partial fulfillment of the requirements of the degree of Master of Arts in Social and Psychological Research, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Remote work; Overload; Employees; Organisational support; Burnout; Work engagement; UCTD; SDG-3: Good health and well-being